Activity space metrics not associated with sociodemographic variables, diet or health outcomes in the Seattle Obesity Study II. (August 2019) - Drewnowski, Adam; Aggarwal, Anju; Rose, Chelsea M.; Gupta, Shilpi; Delaney, Joseph A.; Hurvitz, Philip M.
Abstract: Background: Activity spaces (AS), captured using GPS tracking devices, are measures of dynamic exposure to the built environment (BE). Methods: Seven days of Global Positioning Systems (GPS) tracking data were obtained for 433 adult participants in the Seattle Obesity Study (SOS II). Heights and weights were measured. Dietary intakes from a food frequency questionnaire were used to calculate Healthy Eating Index (HEI 2010) scores. Linear regression analyses examined associations between AS measures: daily route length, convex hull, and radius of gyration, and diet quality and health outcomes, adjusting for covariates. Results: AS measures did not vary by age, gender, race/ethnicity, or socioeconomic status. AS measures were not associated with diet quality or with self-reported obesity or diabetes. One AS measure, route length (in miles), was associated with being employed, living in the suburbs, and with distance and time commuting to work. Conclusion: Spatial mobility studies based on GPS tracking of environmental exposure need to demonstrate a link to relevant health outcomes.